PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK - Faricha Aulia Ananda; Ratna Herawati; Almira Santi Samasta (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to analyze the effect of size of the company, Profitability, Leverage and Sales Growth on Tax Avoidance. The study population is industial companies listed on the Indonesia Stock Exchange in 2018-2021. Data is taken from the financial statements of selected companies by sampling using a purposive sampling method. Before the data were analyzed, a classic assumption test was carried out consisting of the Data Normality Test, the Heteroscedasticity Test, the Auto Correlation Test and the Multicollinearity Test. Data analysis performed was descriptive statistical analysis, t test (partial) and F test with multiple linear regression. The results showed that size of the company and profitability had a significant effect on tax avoidance.